2010
DOI: 10.1021/es100325j
|View full text |Cite
|
Sign up to set email alerts
|

Relating Road Salt to Exceedances of the Water Quality Standard for Chloride in New Hampshire Streams

Abstract: Six watersheds in New Hampshire were studied to determine the effects of road salt on stream water quality. Specific conductance in streams was monitored every 15 min for one year using dataloggers. Chloride concentrations were calculated from specific conductance using empirical relationships. Stream chloride concentrations were directly correlated with development in the watersheds and were inversely related to streamflow. Exceedances of the EPA water quality standard for chloride were detected in the four w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 19 publications
7
53
0
Order By: Relevance
“…Increasing chloride concentrations have been found in lakes (Chapra et al, 2009;Novotny and Stefan, 2009), rivers (Robinson et al, 2003;Kauschal et al, 2005), and groundwater (Mullaney et al, 2009;Eyles and Meriano, 2010) across the northern hemisphere, particularly as a result of the application of deicing salts for winter road maintenance (Chapra et al, 2009;Daley et al, 2009;Trowbridge et al, 2010). Road salt application rates in Vermont state highway districts within the Lake Champlain Basin increased during the 1990s but then declined in more recent years (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Increasing chloride concentrations have been found in lakes (Chapra et al, 2009;Novotny and Stefan, 2009), rivers (Robinson et al, 2003;Kauschal et al, 2005), and groundwater (Mullaney et al, 2009;Eyles and Meriano, 2010) across the northern hemisphere, particularly as a result of the application of deicing salts for winter road maintenance (Chapra et al, 2009;Daley et al, 2009;Trowbridge et al, 2010). Road salt application rates in Vermont state highway districts within the Lake Champlain Basin increased during the 1990s but then declined in more recent years (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Multiple studies have observed chloride concentrations greater than these benchmark concentrations in streams as a result of road salt runoff. These studies have included local (Ruth, 2003;Trowbridge et al, 2010;Allert et al, 2012;Morgan et al, 2012), regional (Kelly et al, 2012b), and national geographic scopes (Corsi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al (2008) reported a threefold concentration increase of chloride in a New York creek over 20 years and estimated that deicing salts, sewage, water softeners and natural background contributed 91, 4, 3 and 2%, respectively. In New Hampshire streams, Trowbridge et al (2010) showed that [90% of the chloride originated from road salt. Imported loads amounted to 45-98 t Cl -km -2 year -1 and were correlated with development in the watershed.…”
Section: Introductionmentioning
confidence: 99%